Global coverage of cetacean line-transect surveys : status quo, data gaps and future challenges - Kaschner, Kristin; Quick, Nicola Jane; Jewell, Rebecca Lucy; Williams, Robert; Harris, Catriona M (PLoS ONE, 2012)
Knowledge of abundance, trends and distribution of cetacean populations is needed to inform marine conservation efforts, ecosystem models and spatial planning. We compiled a geo-spatial database of published data on cetacean abundance from dedicated visual line-transect surveys and encoded >1100 abundance estimates for 47 species from 430 surveys conducted worldwide from 1975-2005. Our subsequent analyses revealed large spatial, temporal and taxonomic variability and gaps in survey coverage. With the exception of Antarctic waters, survey coverage was biased toward the northern hemisphere, especially US and northern European waters. Overall, <25% of the world’s ocean surface was surveyed and only 6% had been covered frequently enough (≥ 5 times) to allow trend estimation. Almost half the global survey effort, defined as total area (km2) covered by all survey study areas across time, was concentrated in the Eastern Tropical Pacific (ETP). Neither the number of surveys conducted nor the survey effort had increased in recent years. Across species, an average of 10% of a species’ predicted range had been covered by at least one survey, but there was considerable variation among species. With the exception of three delphinid species, <1% of all species’ ranges had been covered frequently enough for trend analysis. We use a data-rich species, sperm whale, as an example to illustrate the challenges of using available data from line-transect surveys for the detection of trends or for spatial planning. Finally, we propose and contrast several field and analytical methods to fill in data gaps to improve future cetacean conservation management efforts. Peer reviewed